2013
DOI: 10.1017/sjp.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Affect Schedule: Psychometric Properties for the Brazilian Portuguese Version

Abstract: This study is about the validity and item analysis for the Positive and Negative Affect Schedule (PANAS), respectively through the Exploratory Factor Analysis (principal components method) and the Partial Credit Model (PCM). The scale has been largely used in areas ranging from clinical to social psychology since its release in 1988 by Watson, Clark, and Tellegen. In order to assess validity and item properties (Item Response Theory paradigm), this is study administered PANAS to 354 respondents, 115 male and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 12 publications
2
37
1
9
Order By: Relevance
“…La afectividad negativa se ha asociado a sentimientos como la tristeza, el miedo, la culpa y la ira (Ebesutani et al, 2012;García-Fernández, Inglés, Vicent, Gonzálvez y Mañas, 2013;Pires, Figueiras, Ribas y Santana, 2013), así como a la ansiedad y la depresión (García-Fernández, Martínez-Monteagudo e Inglés, 2013; García-Fernández, Inglés, Gonzálvez, Vicent y Gómez-Núñez, 2013; Robles y Páez, 2003;Watson, Clark y Carey, 1988), siendo distintos los estudios que han obtenido correlaciones positivas de estas variables con los tres primeros factores de la SRAS-R-C (Higa et al, 2002;Kearney y Silverman, 1993).…”
Section: Conclusionesunclassified
“…La afectividad negativa se ha asociado a sentimientos como la tristeza, el miedo, la culpa y la ira (Ebesutani et al, 2012;García-Fernández, Inglés, Vicent, Gonzálvez y Mañas, 2013;Pires, Figueiras, Ribas y Santana, 2013), así como a la ansiedad y la depresión (García-Fernández, Martínez-Monteagudo e Inglés, 2013; García-Fernández, Inglés, Gonzálvez, Vicent y Gómez-Núñez, 2013; Robles y Páez, 2003;Watson, Clark y Carey, 1988), siendo distintos los estudios que han obtenido correlaciones positivas de estas variables con los tres primeros factores de la SRAS-R-C (Higa et al, 2002;Kearney y Silverman, 1993).…”
Section: Conclusionesunclassified
“…The PANAS has been validated in various cultures and in different languages around the world (e.g., Chilean, English, Estonian, German, Hungarian, Japanese, Portuguese, Romanian, Russian, Spanish, and Turkish) and the results have consistently shown good psychometric properties (Carvalho et al, 2013;Cotigă, 2012;Crawford & Henry, 2004;Dufey & Fernandez, 2012;Galinha, Pereira, & Esteves, 2014;Gyollai, Simor, Koteles, & Demetrovics, 2011;Pires, Filgueiras, Ribas, & Santana, 2013;Sandín et al, 1999;Terracciano, McCrae, & Costa, 2003). Currently, different versions of this measure are available, such as an extended and a shorter version compared to the original PANAS (e.g., Cotigă, 2012;MacKinnon et al, 1999), and one for children (e.g., Huebner & Dew, 1995;Crawford & Henry, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, different versions of this measure are available, such as an extended and a shorter version compared to the original PANAS (e.g., Cotigă, 2012;MacKinnon et al, 1999), and one for children (e.g., Huebner & Dew, 1995;Crawford & Henry, 2004). Several versions of the PANAS have also been validated for Portuguese-speaking samples (Carvalho et al, 2013;Galinha, Pereira, & Esteves, 2014;Galinha & Pais-Ribeiro, 2005;Pires, Filgueiras, Ribas, & Santana, 2013), with good psychometric properties, and these reliably measured two distinct dimensions (PA and NA), based on the earlier work by Watson and his colleagues (1988). Additionally, previous research revealed some validations of the PANAS among small older samples (Albuquerque, Sousa, & Martins, 2010;Buz, Pérez-Arechaederra, Fernández-Pulido, & Urchaga, 2015;Nolla, Queral, & Miró, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have developed and discussed the psychometric properties of the positive and negative affect scale (PANAS) (Chin, 2009;Chiu, Hung, & Chou, 2013;Pires, Filgueiras, Ribas, & Santana, 2013;Ebesutani, Okamura, Higa-McMillan, & Chorpita, 2011). Chin (2009) developed an instrument for assessing students' affect toward science writing and found that the instrument had the psychometric properties of reliability and validity in a sample of Taiwanese university students.…”
Section: Introductionmentioning
confidence: 99%